EVALUASI PROGRAM KONVERSI MINYAK TANAH KE LPG (LIQUEFIED PETROLEUM GAS) DI KELURAHAN TEMBALANG, KEC. TEMBALANG, KOTA SEMARANG - Pamaria Hendri; Margaretha Suryaningsih; Ida Hayu Dwimawanti (Journal of Public Policy and Management Review, 2013)
Kerosene to LPG program in Kelurahan Tembalang is a program of the central government. This program is an effort by the government to address the heightened oil prices and depleting the availability. World oil prices are rising, affecting the size of the state budget for it, the government convert kerosene to LPG. In addition, the abundant presence of LPG in Indonesia and has not been used optimally. Kerosene to LPG is intended for the middle class and small kerosene users.The purpose of this study was to evaluate and analyze the conversion program from kerosene to LPG in Kelurahan Tembalang, so it can be seen that the impact occurred, success factors, barriers, and recommendations of the program further. The evaluation program is based on indicators by William N Dunn which include: equity, adequacy, and accuracy and indicators according to a LAN that includes: input, output, outcome, benefits and impacts. In this study, researchers used a snowball sampling technique. Data collection method used is in-depth interview techniques, observation and study documentation.This study suggests that the conversion program from kerosene to LPG in Kelurahan Tembalang has both positive and negative. The positive effect is caused by the public convenience and saving of expenditure, while the negative effects are elderly people who are afraid to use LPG 3 kg. Kerosene to LPG in Kelurahan Tembalang running less successful because most of the middle above the target program and the people are reluctant to use LPG. Inhibiting factor is the lack of monitoring of the government, the state of society with poor conditions, 3 kg LPG price in excess of HET.